A review of the genus Abaxisotima Gorochov, 2005 (Orthoptera: Tettigoniidae: Phaneropterinae) - Wang, Gang; Shi, Fu-Ming (Zootaxa, 2009)
A key to species of the genus Abaxisotima Gorochov, 2005 is presented and a new species, i.e. Abaxisotima spiniforma sp. nov is described. We also provide a supplementary description of Abaxisotima bicolor (Liu, Zheng & Xia, 1991). All specimens are deposited in the Museum of Hebei University.